Structure, function, and research progress of primary cilia in reproductive physiology and reproductive diseases - Long, Xiaochuan; Chen, Li; Xiao, Xinyao; Min, Xiayu; Wu, Yao; Yang, Zengming; Wen, Xin (Frontiers in Cell and Developmental Biology, 2024)
Primary cilia, serving as the central hub for cellular signal transduction, possess the remarkable ability to translate diverse extracellular signals, both chemical and mechanical, into intracellular responses. Their ubiquitous presence in the reproductive system underscores their pivotal roles in various cellular processes including development, differentiation, and migration. Emerging evidence suggests primary cilia as key players in reproductive physiology and associated pathologies. Notably, primary cilia have been identified in granulosa cells within mouse ovaries and uterine stromal cells, and perturbations in their structure and function have been implicated in a spectrum of reproductive dysfunctions and ciliary-related diseases. Furthermore, disruptions in primary cilia-mediated signal transduction pathways under pathological conditions exacerbate the onset and progression of reproductive disorders. This review provides a comprehensive overview of current research progress on primary cilia and their associated signaling pathways in reproductive physiology and diseases, with the aim of furnishing theoretical groundwork for the prevention and management of primary cilia-related structural and functional abnormalities contributing to reproductive system pathologies.